Thomas D. White papers - White, Thomas D. (Thomas Dresser), 1901-1965.
Correspondence, speeches, reports, statements, reading files, and other papers relating chiefly to White's service as U.S. Department of the Air Force Chief of Staff. Includes speeches and statements made before congressional committees, especially on the subject of air power needs and capabilities. Correspondents include Joseph H. Atkinson, W. Barton Leach, Curtis E. LeMay, Thomas S. Power, Walter E. Todd, and Ennis Clement Whitehead.
Air Force officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Atkinson, Joseph H. -- 1900-1984 -- Correspondence; Leach, W. Barton -- 1900- -- Correspondence; LeMay, Curtis E. -- Correspondence; Power, Thomas S. -- 1905- -- Correspondence; Todd, Walter E. -- 1906-1978 -- Correspondence; Whitehead, Ennis Clement, -- 1895-1964 -- Correspondence; United States. -- Department of the Air Force. -- Chief of Staff; Air power; Air Force officers